Karakteristik Pelanggaran Pemilihan Kepala Daerah Kabupaten Lombok Timur Tahun 2013 Perspektif Good Governance - Abdul Qodir Jaelani (UIN Sunan Kalijaga Yogyakarta, 2014)
The general election is a manifestation of the people‟s softreight in order toproduce a democratic goverment, elections that are direct, general, free, confidential,honest and fair can only be realized if the election management has high integrity andunderstand and respect the civil and political rights of citizens. Weak electionpotentially undermined qualified election organizers have a duty to hold elections byinstitutional national, permanent and independent. One of the importan factors for thesuccess of election it self, the election commission, ellaction watchdog, and honorary boardof election.